Evaluation of Indian myrrh (Commiphora wightii) landraces for hyper arid Thar desert - MERTIA, R S; SINHA, N K; KANDPAL, B K; SINGH, DALEEP (The Indian Journal of Agricultural Sciences, 2010)
A study was carried out at the research farm of the Central Arid Zone Research Institute, Jaisalmer, during 2005–09 to evaluate 5 landraces of Indian myrrh [Commiphora wightii (Arn.) Bhandari], namely ‘Dantiwara’, ‘Mangaliawas’, ‘Kukma-Bhuj’, ‘Bhind-Murena’ and ‘Jaisalmer Local’ in relation to changes in growth behaviour and total phenol content in 4-year-old planted plants. Out of all the 5 landraces, plant height (197.4 cm), number of branches (9.3), Stalk collar diameter (62.2 mm), main stem diameter and crown spread (266.5 cm) was recorded significantly higher in ‘Mangaliawas’, followed by ‘Jaisalmer Local’, ‘Dantiwara’, ‘Kukma-Bhuj’ and ‘Bhind-Murena’ in all the successive years. Maximum amount of phenol was recorded in ‘Jaisalmer Local’. Hence ‘Mangaliawas’, ‘Jaisalmer Local’ and ‘Dantiwara’ can be used for hyper arid situation at Thar desert.